The kinase Bud32 regulates iron homeostasis in fungal pathogen Cryptococcus neoformans - Ma, Yuanyuan; Pan, Bo; Lei, Wenzhi; Fang, Wenjie; Pan, Weihua; Liao, Wanqing; Xu, Bin; Xue, Peng (Frontiers in Immunology, 2025)
IntroductionThe ability to acquire iron and maintain iron homeostasis is crucial for the virulence of the human pathogenic fungus Cryptococcus neoformans. This study investigates the role of Bud32, a core virulence kinase and component of the KEOPS complex, within the iron regulatory network of C. neoformans.MethodsWe used gene deletion techniques to study the phenotypic effects of BUD32 gene knockout and conducted proteomic and metabolomic analyses to assess changes in protein expression and metabolite levels in the mutant. Additionally, we performed in vivo phosphoproteomics analysis to evaluate Bud32 impact on iron regulatory proteins.ResultsOur findings revealed that deletion of BUD32 gene significantly impaired growth in iron-limiting environments, leading to notable alterations in the expression of iron transport and iron-sulfur cluster (ISC)-containing proteins. Specifically, Bud32 was shown to modulate ISC assembly and influence the activity of key iron-sulfur binding proteins, including Grx4, Cir1, and HapX. Metabolic profiling indicated changes in 696 metabolites, with reductions in biliverdin levels. Additionally, BUD32 gene deletion resulted in widespread changes in the phosphorylation status of numerous proteins, including the iron regulators Cir1 and Rim101.ConclusionThese findings provide evidence for the involvement of the kinase Bud32 in regulating iron homeostasis in C. neoformans, thereby contributing to our understanding of its virulence mechanisms.